Branding and agricultural value chains in developing countries: insights from Bihar, India - Minten, Bart; Singh, K.M.; Sutradhar, Rajib (International Food Policy Research Institute, 2012)
Local brands are rapidly gaining agricultural market share in developing countries. However, it is not well understood how they reshape agricultural value chains and what the implications are for consumers and producers. In a detailed case study of the value chain of makhana in Bihar, we see the fast emergence —a doubling over five years—of more expensive packed and branded products. The effect on consumers is ambiguous. While the emergence of brands leads to increasing differentiation in retail markets, the brands in these settings provide mostly incomplete or misleading information for the consumer, and the quality of products contained in branded bags is often lower than for loose products. We also find that farmers realize few direct benefits from the presence of these brands.